Factors accelerating recurrences and secondary tumors in cutaneous squamous cell carcinoma. Issue 4 (April 2021) - Rahimi-Nedjat, Roman Kia; Tuettenberg, Andrea; Sagheb, Keyvan; Loquai, Carmen; Rybczynski, Benedict; Grabbe, Stephan; Walter, Christian; Al-Nawas, Bilal
Abstract: To investigate factors that affect and also decrease the duration for recurrences and secondary tumors in cSCC. A retrospective study was conducted for all patients who were treated for a cSCC of the head and neck between 2009 and 2016. Anamnestic as well as epidemiological and histological data were noted and correlated with the occurrence of recurrences and secondary cancers. The duration between surgery and these events was used to determine if histological factors accelerate their occurrence. The highest risk for recurrences was seen in patients with previous skin cancers (RR 3.23). Histological ulceration (p = 0.003) and grading (p = 0.031) of the tumor were found as significant factors accelerating the time to relapse. Surrounding chronic precancerotic lesions (p < 0.001) and poor tumor grading (p = 0.035) were found as significant factors accelerating the time until a secondary cSCC was observed. Known risk factors increase not only the risk for a cSCC but also for recurrences. Specific histologic findings can help to adjust follow-up intervals to identify recurrences and secondary tumors at an early stage as these were shown to decrease the duration for a further event.